Do cellmates matter?: a causal test of the schools of crime hypothesis with implications for differential association and deterrence theories - Harris, Heather M. (Criminology, 2018)
In the schools of crime hypothesis, social interactions between inmates are assumed to produce criminogenic rather than deterrent prison peer effects, thus implicating them in the persistence of high recidivism rates and null or criminogenic prison effects. We assess the validity of the schools of crime hypothesis by estimating prison peer effects that result from differential cellmate associations in a male, first‐time release cohort from the Pennsylvania Department of Corrections. To isolate causal prison peer effects in the presence of essential heterogeneity, we use a semiparametric local instrumental variables estimation strategy. Our results do not support the school of crime hypothesis. In our sample, prison peer effects produced in interaction with more criminally experienced cellmates are always null or deterrent rather than criminogenic. Although we do not explicitly test for the operant conditioning mechanisms theorized to underlie social influence in the context of differential association, we argue that, under the assumption that the differential association context relates positively to the direction of peer influence, our universally noncriminogenic estimates exclude direct reinforcement, vicarious reinforcement, and direct punishment as potential drivers of prison peer effects produced in interaction with more criminally experienced cellmates. Our results support the assertion that operant conditioning mechanisms connect differential association and deterrence theories.